The epidemiology and importance of vitamin B12 screening in diabetic patients - Yamani, Abrar A. A.; Awadain, Jameel A.; Saleh, Yousif A. A.; Baothman, Mohammad S.; Alhussainy, Feras H.; Alshehri, Mazen S.; Alharthi, Helal J.; Alqwizani, Abdulmalek R.; Alrehaili, Abdulrahman A.; Melebary, Ruwaidah H.; Alanazi, Manar H. (International Journal Of Community Medicine And Public Health, 2021)
Peripheral neuropathy is a commonly reported chronic adverse event among diabetes mellitus (DM) patients secondary to poor glycemic control. It might also result secondary to deficiency of vitamin B12, reportedly common among diabetic patients. Deficiency of vitamin B12 might result from prolonged metformin administration in patients with type II DM (T2DM). It might also result from reduced absorption and impaired metabolism-related events in type I DM (T1DM) patients. This occurs secondary to the presence of associated autoimmune disorders. Vitamin B12 deficiency is a commonly encountered condition among diabetic patients, both T1DM and T2DM, with variable etiologies. Our current study discussed the epidemiology and importance of screening of vitamin B12 in these patients. However, our findings show that screening is not commonly practiced in different settings. Therefore, awareness is low about the benefits and complications of this practice. Therefore, further research is encouraged to alleviate the quality of care in diabetic patients. Screening for vitamin B12 deficiency might intervene against any potential complications, including irreversible, painful, and potentially disabling nerve injury. Accordingly, it is recommended that screening should be initiated since the start of metformin administration and every year or when relevant clinical manifestations were reported.